Gender and power in land use choices in agrobiodiversity conservation: Lessons from the multifunctional landscapes of Mbire District, Zimbabwe - Zingwena, Taurai; Manyanga, Mark; Odjo, Sylvanus; Chimonyo, Vimbayi Grace Petrova (CIMMYT, 2025)
Gendered power relations critically shape land-use choices, labour allocation, and agrobiodiversity outcomes in smallholder farming systems, yet they remain underexamined in landscape-level interventions. This paper analyses how intra-household gender dynamics influence participation, decision-making authority, and access to resources in agrobiodiversity conservation within the multifunctional landscapes of Mbire District, Zimbabwe. Using a qualitative research design, the study draws on gender-segregated focus group discussions with 49 participants across two wards, followed by a joint deliberative dialogue. Analysis is guided by the TASSFA framework (Tasks, Authority, Spaces, Skills, Frequencies, and Access) to systematically examine gendered roles, constraints, and power relations embedded in everyday land-use practices. The findings reveal a persistent disconnect between labour contributions and decision-making power. Women perform a substantial share of productive and reproductive labour related to agrobiodiversity management, yet men retain dominant authority over strategic decisions, land control, and benefit allocation. Although households frequently describe decision-making as “joint,” closer analysis shows that jointness often reflects consultation rather than equal authority. Gendered exclusions are reinforced through restricted access to decision spaces, unequal recognition of skills, time poverty, and limited access to markets and assets. The study suggests that effective and equitable landscape interventions must move beyond participation to explicitly address power, authority, and access, positioning TASSFA as a valuable tool for gender-transformative multifunctional landscape governance.